Understanding the support for gender-based harassment perpetrators: the role of closeness and empathy - Borges-Castells, Nira; Betancor, Verónica; Rodríguez-Pérez, Armando (Frontiers in Psychology, 2024)
Gender-based harassment is a pressing social challenge urgently demanding eradication. While social movements emphasize supporting victims, societal responses sometimes lean toward exculpating perpetrators. This study examines two factors influencing this exoneration: closeness to perpetrators and empathy focus. A total of 345 participants took part in an experimental design to assess how closeness to perpetrators (close vs. distant) and empathy focus (on the perpetrator vs. victim vs. control) impact the moral justification of harassment and the dehumanization of both parties. Results indicate that closeness and empathizing with perpetrators lead to greater leniency-more moral justification and less dehumanization of the perpetrator. Heightened moral justification for close perpetrators is mediated by increased empathy toward them and decreased empathy for victims, and reduced dehumanization of close perpetrators corresponds to heightened empathy toward them. This research highlights how closeness and empathy, two initially positive factors, can foster tolerance toward gender harassment.